Hubungan Timbal Balik antara Perguruan Tinggi dan Sekolah serta Masyarakat - Rapiko, Rapiko; El Hilali, Husni; Usmar, Ali; Sundara, Vinny Yuliani; Zulyanty, Marni; Mardia, Ainun; Mubarak, Fadhlul; Nurniswah, Nurniswah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this activity among them is implementing service to the community in the form of providing free mathematics study guidance for students of class VI of Nurul Khoir Private Elementary School, knowing the impact of service as well as knowing the barriers as well as knowing the influence of reciprocal relationship between the college and the community, the school. This dedication to the community consists of a team of lecturers and students of Mathematics Tadris Faculty of Education and Teachers of UIN Sultan Thaha Saifuddin Jambi. This devotion was implemented at SDN 133/IX Hill Baling. Dedication is done by providing free mathematics study guidance to the students of class VI for the preparation of facing the National Examination. This free study guidance was implemented over 12 meetings by conducting a pre-test at the first meeting and a post-test at the last meeting. These community service activities provide a virtuous reciprocal relationship between the college, school and community. Schools and communities get the knowledge and experience to prepare well for UN mathematics as well as colleges get appropriate curriculum related evaluation and adaptation in order to improve the students’ ability to face UN mathematics.